The Promises and Pitfalls of Retrieval-Extinction Procedures in Preventing Relapse to Drug Seeking - McNally, Gavan P.; Hutton-Bedbrook, Kathryn E. (Frontiers in Psychiatry, 2013)
Relapse to drug seeking after treatment or a period of abstinence remains a fundamental challenge for drug users. The retrieval – extinction procedure offers promise in augmenting the efficacy of exposure based treatment for drug use and for protecting against relapse to drug seeking. Preceding extinction training with a brief retrieval or reminder trial, retrieval – extinction training, has been shown to reduce reinstatement of extinguished drug seeking in animal models and also to produce profound and long lasting decrements in cue-induced craving in human heroin users. However, the mechanisms that mediate these effects of retrieval - extinction training are unclear. Moreover, under some circumstances, the retrieval – extinction procedure can significantly increase vulnerability to reinstatement in animal models.